Fingerprinting the Asterid species using subtracted diversity array reveals novel species-specific sequences. - Nitin Mantri (Public Library of Science (PLoS), 2012)
Background Asterids is one of the major plant clades comprising of many commercially important medicinal species. One of the major concerns in medicinal plant industry is adulteration/contamination resulting from misidentification of herbal plants. This study reports the construction and validation of a microarray capable of fingerprinting medicinally important species from the Asterids clade. Methodology/principal findings Pooled genomic DNA of 104 non-asterid angiosperm and non-angiosperm species was subtracted from pooled genomic DNA of 67 asterid species. Subsequently, 283 subtracted DNA fragments were used to construct an Asterid-specific array. The validation of Asterid-specific array revealed a high (99.5%) subtraction efficiency. Twenty-five Asterid species (mostly medicinal) representing 20 families and 9 orders within the clade were hybridized onto the array to reveal its level of species discrimination. All these species could be successfully differentiated using their hybridization patterns. A number of species-specific probes were identified for commercially important species like tea, coffee, dandelion, yarrow, motherwort, Japanese honeysuckle, valerian, wild celery, and yerba mate. Thirty-seven polymorphic probes were characterized by sequencing. A large number of probes were novel species-specific probes whilst some of them were from chloroplast region including genes like atpB, rpoB, and ndh that have extensively been used for fingerprinting and phylogenetic analysis of plants. Conclusions/significance Subtracted Diversity Array technique is highly efficient in fingerprinting species with little or no genomic information. The Asterid-specific array could fingerprint all 25 species assessed including three species that were not used in constructing the array. This study validates the use of chloroplast genes for bar-coding (fingerprinting) plant species. In addition, this method allowed detection of several new loci that can be explored to solve existing discrepancies in phylogenetics and fingerprinting of plants.